Mdm30 Is an F-Box Protein Required for Maintenance of Fusion-competent Mitochondria in Yeast - Fritz, Stefan (The American Society for Cell Biology, 2003)
Mitochondrial fusion and fission play important roles for mitochondrial morphology and function. We identified Mdm30 as a novel component required for maintenance of fusion-competent mitochondria in yeast. The Mdm30 sequence contains an F-box motif that is commonly found in subunits of Skp1-Cdc53-F-box protein ubiquitin ligases. A fraction of Mdm30 is associated with mitochondria. Cells lacking Mdm30 contain highly aggregated or fragmented mitochondria instead of the branched tubular network seen in wild-type cells. Δmdm30 cells lose mitochondrial DNA at elevated temperature and fail to fuse mitochondria in zygotes at all temperatures. These defects are rescued by deletion of DNM1, a gene encoding a component of the mitochondrial division machinery. The protein level of Fzo1, a key component of the mitochondrial fusion machinery, is regulated by Mdm30. Elevated Fzo1 levels in cells lacking Mdm30 or in cells overexpressing Fzo1 from a heterologous promoter induce mitochondrial aggregation in a similar manner. Our results suggest that Mdm30 controls mitochondrial shape by regulating the steady-state level of Fzo1 and point to a connection of the ubiquitin/26S proteasome system and mitochondria.